DIAGNOSTIC AND PROGNOSTIC VALUE OF CIRCULATING miRNAs AS NON-INVASIVE BIOMARKERS IN GLIOBLASTOMA MULTIFORME: A SYSTEMATIC REVIEW AND META-ANALYSIS - Akas, Ignasius Dede Setyo; Seleky, Cherlyn; Febriani, Reka; Titaley, Christiana Rialine; Huwae, Laura Bianca Sylvia (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Glioblastoma multiforme (GBM) is most prevalent and aggressive form of glioma, characterized by a high mortality rate and significant effect on patient's quality of life. The challenges in diagnosing, treating, and predicting prognosis of GBM highlight the need for more reliable biomarkers. Promising characteristics as noninvasive biomarkers have been identified in microRNA (miRNAs) to their critical role in glioblastoma pathogenesis. Objective: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 standards guided implementation of this systematic review and meta-analysis examining diagnostic and prognostic relevance of microRNAs in GBM as non-invasive biomarkers. A total of 9 studies on diagnostic accuracy and 6 studies on prognostic analysis were included. Articles were identified through comprehensive searches in PubMed, EBSCO, and Wiley databases. Availability of diagnostic indicators such as area under curve (AUC), sensitivity, and specificity for miRNA-based diagnosis, along with survival measurements reported as hazard ratios (HRs) or mean survival outcomes, constituted main inclusion requirements for original studies. Results: In meta-analysis, circulating miRNAs achieved notable diagnostic performance, supported by sensitivity and specificity values of 0.86 and 0.92, respectively, along with AUC of 0.93. Subgroup analysis was then performed to assess consistency of accuracy based on ethnicity, sample source, dysregulation category, and miRNA profile mapping. Certain miRNAs also showed promise as prognosis markers as they are involved in glioblastoma progressivity. Conclusion: Circulating miRNAs demonstrate high accuracy as non-invasive biomarkers for GBM diagnosis and prognosis. Their role in glioblastoma progression suggests potential applications in more precise therapeutic approaches.